The determinants of labor outmigration in tea plantation sector in badulla district - Dharmadasa, R.A.P.I.S.; De zoysa, M. (University of Jaffna, 2012)
This study is an attempt to find out the determinants of labor outmigration from tea plantation sector in Badulla District. A simple random sample of 378 households was drawn from the total worker population of the selected tea estates. The data were gathered using pretested questionnaire and a logistic regression model was estimated to find the determinants of migration. Results suggests that experience of household head in tea estate work, family size, total income from tea, number of dependents in a family and race affect the migration decision negatively. Hence higher the non farm income higher will be the propensity to migrate.
Keywords: Logistic regression; Outmigration; Tea estate sector